S=10 km
S₁₁=7 km
v₁₁=18 km/h
v₁₂=12 km/h
v₂=15 km/h
Pierwszy biegacz
S₁₂=S-S₁₁=10-7=3 km
[tex]t_{11}=\frac{S_{11}}{v_{11}}=\frac{7 \ [km]}{18 \ [\frac{km}{h}]}=0,3(8) \ h[/tex]
[tex]t_{12}=\frac{S_{12}}{v_{12}}=\frac{3 \ [km]}{12 \ [\frac{km}{h}]}=0,25 \ h[/tex]
[tex]t_1=t_{11}+t_{12}=0,63(8) \ h=38,(3) \ min[/tex]
Drugi biegacz
[tex]t_2=\frac{S}{v_2}=\frac{10 \ [km]}{15 \ [\frac{km}{h}]}=0,(6) \ h=40 \ min[/tex]
Na metę jako pierwszy dotarł biegacz "pierwszy" niespełna dwie minuty wyprzedzając konkurenta.